2016
DOI: 10.1002/smll.201600725
|View full text |Cite
|
Sign up to set email alerts
|

A Single‐Cell Assay for Time Lapse Studies of Exosome Secretion and Cell Behaviors

Abstract: To understand the inhomogeneity of cells in biological systems, there is a growing demand on the capability of characterizing the properties of individual single cells. Since single cell studies require continuous monitoring of the cell behaviors instead of a snapshot test at a single time point, an effective single-cell assay that can support time lapsed studies in a high throughput manner is desired. Most currently available single-cell technologies cannot provide proper environments to sustain cell growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 35 publications
1
70
1
Order By: Relevance
“…While few studies have monitored exosome secretion rate, our control numbers corroborate those seen in cell lines [44]. For example, a recent study reported secretion rate of 4 3 10 8 exosomes per 100,000 cells per 24 hours in MCF10A cell lines [45]. Flow cytometry of exosomes revealed two important conclusions.…”
Section: Discussionsupporting
confidence: 83%
“…While few studies have monitored exosome secretion rate, our control numbers corroborate those seen in cell lines [44]. For example, a recent study reported secretion rate of 4 3 10 8 exosomes per 100,000 cells per 24 hours in MCF10A cell lines [45]. Flow cytometry of exosomes revealed two important conclusions.…”
Section: Discussionsupporting
confidence: 83%
“…To enrich the secretions, Chiu et al resorted to a bioprinting method, in which glass slides were modified with capture antibodies and then placed on microwells. The exosomes secreted from corresponding single cells below could be collected and subsequently measured by streptavidin quantum dots …”
Section: Single‐cell Isolationmentioning
confidence: 99%
“…Thus each protein could also gain unique fluorescent barcoding as the corresponding microbead, rendering this strategy to reach exponential growth for protein targets . Fluorescence readout exhibits a simple and rapid approach of protein measurement, and is especially suitable for secretions detection, but still suffers from limited complexity and low sensitivity when detecting low‐copy proteins.…”
Section: Single‐cell Omics Analysismentioning
confidence: 99%
“…A chip size between 5 x 5 mm 2 and 12 x 12 mm 2 is recommended. A cell loading chip made of PDMS is also recommended (Chiu et al ., 2016). …”
Section: Introductionmentioning
confidence: 99%
“…After each collection, anti-body conjugated quantum dots are used to label exosomes to allow counting and analysis of exosome surface proteins. Detailed studies of exosome properties related to cell behaviors such as responses to drugs and stress at single cell resolution can be found in the publication (Chiu et al ., 2016). …”
mentioning
confidence: 99%